Efficacy of frontalis suspension with silicone rods in ptosis patients with poor Bell's phenomenon - Khyati P Shah (Taiwan Journal of Ophthalmology, 2017)
Purpose: The purpose of the study was to evaluate the efficacy of silicone rods as frontalis sling for correction of ptosis associated with poor Bell's phenomenon in specific situations. Materials And Methods: A retrospective interventional case series of 25 eyes of 19 patients who underwent frontalis suspension surgery with silicone rods for ptosis correction from May 2006 to April 2011, was performed. Inclusion criteria included severe ptosis with poor Bell's phenomenon. Patient evaluation included clinical history and other relevant parameters of ptosis measurement. Final outcome measurements included postoperative lid height, lagophthalmos, complications, need for reoperation, and patient satisfaction. Results: Mean age at presentation was 25.72 ± 2.2 years. The sex ratio of male: female was 1.11. The causes of ptosis included chronic progressive external ophthalmoplegia (CPEO) in 11 eyes (44%), oculopharyngeal dystrophy in 2 (8%), third cranial nerve palsy in 7 (28%), traumatic in three eyes (12%), and iatrogenic postoperative ptosis (after orbital tumor excision) in two eyes (8%). The postoperative palpebral fissure height and margin reflex distance improved significantly (P = 0.0001). Extrusion of the sling and granuloma formation occurred in two eyes each, and these patients had to undergo sling removal. One patient developed mild exposure keratopathy and was managed conservatively. Conclusion: Silicone is an effective material for use in frontalis suspension in the management of severe ptosis with poor Bell's phenomenon. The elastic nature of silicone rod makes it an ideal suspensory material for patients with CPEO or third nerve palsy.